(3afhf GdYQV GdeSQMj h efGgL GdHMK (B/s ((3GdEScfOQjI (B:s (3OGQ GdhaGA dOfjG GdWHGYI h GdfTQ ,s, 2004)
(3jJfGhd fXGe OQGSI GdeSQM aj bSe GdeSQM HGOGH GdGScfOQjI h OQGSJg aj LGeYI Gdedc SYhO QjGV h jhGRf HjfgG LejYG aj SHjd JWhjQ GdJYdje GdLGeYj aj Pdc GdaQY GdJNUUjs
Keywords: (3GdeSQMs; (3Gdafhf s